PENGARUH PEMBERIAN PUPUK NPK GROWER DAN DEFOLIASI TERHADAP PERKEMBANGAN BIJI DAN PRODUKSITANAMAN JAGUNG (Zea mays L.) - Prihatin Ponco Pamungkas; Maizar Maizar; Sulhaswardi Sulhaswardi (UIR Press, 2017)
The study aimed to determine the effect of giving NPK Grower fertilizer and defoliation to seed development and corn crop production. The design used in this study was a Factorial Completely Randomized Design consisting of two factors. The first factor is NPK Grower (N) fertilizer with a dose of 0, 7.5, 15, 22.5g / plant while the second factor is Defoliation (D) with some 0, 2, 4, all leaves under the cob. The parameters observed were changes in seed dry weight (g), changes in seed moisture content (%), speed of accumulation of dry matter (mg / seeds / day), effective filling time (days), harvest age (days), and dry shelled weight ( g). The last observation data were analyzed statistically and continued with a BNJ follow-up test at the level of 5%. The results showed that interactively giving NPK Grower and Defoliation fertilizer had a significant effect on changes in seed dry weight, changes in seed moisture content, speed of dry matter accumulation, harvest age and dry shell weight. The best treatment is in the combination of 22.5g / plant NPK Grower fertilizer treatment and Defoliation of all leaves under the cob (N3D3). The main effect of NPK Grower fertilizer has a significant effect on all parameters. The best treatment for NPK Grower fertilizer is 22.5g / plant (N3). The main effect of Defoliation has a significant effect on all parameters. Best treatment Defoliate all leaves under the cob (D3).